Sound absorption for concrete containing polyethylene terephthalate waste - Kai Loong, Tam; Shahidan, Shahiron; Abdul Manaf, Adib Fikri; Khalid, Faisal Sheikh; Mohd Zuki, Sharifah Salwa; Abd Rahim, Mustaqqim; Wan Ibrahim, Mohd Haziman; Adnan, Suraya Hani; A. Mijarsh, Mustafa Juma; Mohammad Azmi, Mohamad Azim (Innovare Academics Sciences PVT. LTD, 2020)
Plastic solid waste generation increases every year with the current consumption habit prevalent in society nowadays. The improper disposal of plastic has been a major concern to the environment as it is not easily degradable. The issue of environmental pollution caused by polyethene terephthalates (PET) has been extensively discussed and the best solution proposed is recycling. Fibre Concrete (FC) was a composite material resulting from the addition of fibres to ordinary concrete. The objective of this research was to determine the acoustic absorption coefficient of concrete containing 0%, 0.5%, 1.0%, 1.5%, 2.0% of PET fibre compared to normal concrete. In this study, straight and irregular recycled PET fibres were used. The fibres were simply cut from PET plastic bottles. The length and width of recycling PET fibre were fixed at 25 mm and 5 mm respectively. The chosen percentages were 0.5%, 1.0%, 1.5% and 2.0% of fiber. A water-cement ratio of 0.45 was acceptable for all ranges. The tests that were conduct include the slump test, compression test, and impedance tube test. The specimens were tested on day 7 and day 28 after the concrete is mixed. The end of this research results for the compressive strength of normal concrete after 28 days of curing was 48.2 MPa while concrete with 0.5% PET, 1.0 % PET, 1.5% PET and 2.0% PET recorded a compressive strength of 50.9 MPa, 49.8 MPa, 47.9 MPa and 46.6 MPa respectively. The result of the impedance test received at age 28 days was 0.13 for normal concrete and 0.16, 0.14, 0.16 MPa, and 0.14 for 0.5% PET, 1.0 % PET, 1.5% PET and 2.0% PET respectively. In conclusion, the aspect ratio of the fibres to the concrete must be correlated to avoid reducing durability. In conclusion, the addition of 0.5% PET recycled fibre into concrete showed the best value in terms of strength and 0.16 for the sound absorption coefficient.